(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
As tertiary institutions globally transitioned into an online teaching framework as a consequence of the Covid-19 pandemic, it is critical that history education lecturers reconsider their teaching and learning strategies. This article reports on the planning and implementation of an online teaching programme within the History in Education subject group at the North-West University (NWU), in South Africa. The author is the subject group leader of the subject group and from observations and experiences, this article will report on how this program was implemented. First and foremost, how we handled teaching in an online setting is vastly different from a face-to-face setting. Few lecturers might have taught students studying in distance programs for some time, but for many lecturers and students who are accustomed to face-to-face instruction, the online world may often be new and even intimidating. The existing scenario calls for a full rethink in teaching and learning. Through proper preparation, we will not only provide our lecturers through greater versatility in the delivery of online classrooms, but also represent our students when making the best of the opportunities we have at our disposal. This article wishes to undertake a critical experiential evaluation of this online teaching strategy that was used in 2020 in the History Education subject group at the North-West University. A literature review focusing on online teaching, History in Education online teaching as well as COVID-19’s impact on tertiary education. The methodology of the research is then discussed, followed by the initial planning stage, culminating in the lessons learned and possible future changes to this plan.